Market Dynamics in Sypply Chains: The Impact of Globalization and Consolidation on food companies' mark-ups - Eleni A. Kaditi (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
This paper examines whether ownership and increased competitive pressure affect food retailers' market power, analysing whether all actors involved in the food supply chain deviate from the pricing behaviour that exists under perfect competition. A method proposed by Roeger (1995) is used to estimate price-cost margins, relaxing the assumptions of perfect competition and constant returns to scale. The obtained results show that foreign investments and consolidation have a positive and significant impact on the market power of food processors and retailers. Food processors, agricultural producers and wholesalers have lower price-cost margins than retailers, which suggests that these actors price closer to marginal costs being more concerned with maximising social welfare or that the firmer have higher costs than retailers. The results are robust to various estimation techniques and specifications.
Keywords: F23; L13; L81; 330; Price-cost mark-ups; multinational firms; retailing; Nahrungsmittelmarkt; Nahrungsmittelpreispolitik; Mark-up Pricing; Betriebliche Preispolitik; Griechenland